The elongation of beams in reinforced concrete special moment resisting frames - Liuzza, Gabrielle (Kansas State University, 2018)
Special moment resisting frames (SMRF) are intended to protect the structure from earthquake motions through a ductile inelastic response. This thesis evaluates the performance of reinforced concrete SMRFs with an emphasis on the second level beams. Due to previous research, it is concluded that two-dimensional finite element analyses (2D-FEA) and three-dimensional finite element analyses (3D-FEA) have different results when evaluating the same structure. Due to this, the thesis used a 3D-FEA to analyze frames based on Design Example 7 in the 2006 IBC Structural/Seismic Design Manual (Appendix A). While looking at the frame as a whole, the first of two parametric studies was performed over the columns. Using LS-DYNA the columns’ forces, displacement, moment, and curvature were evaluated. From these results, it was concluded that in SMRF, columns are not acting per current design assumptions due to the elongation of beams. Using the knowledge gained in the first parametric study, a second parametric study was performed on the second level floor beams. Focusing on the beam elongation, this thesis evaluates multiple frames with different load combinations using LS-DYNA to find the displacement of the reinforcement in the beams. With the results, an equation to calculate the elongation of beams was proposed, as well as an average percentage of the elongation in reinforced concrete SMRF. The equation and average percentage of elongation aim to provide a standard design consideration for the elongation of beams.
Keywords: Reinforced concrete; Special moment resisting frames; Beam elongation; Column rotation; Neutral axis; Beam deformation